‘They Were Surprised That Such Jobs Even Exist…’ Supporting Students’ Career Awareness During Learning Activities at Museums and Environmental Education Centres - Helene Uppin; Inge Timoštšuk (Social Sciences)
Many factors influence students’ career awareness and future career choices. Curricula-related learning activities that entail boundary-crossing between formal and nonformal contexts, such as museums and environmental education centres, can also broaden perspectives. Out-of-school learning can unveil career trajectories, introduce professions, spark interest in new topics, and support lifelong learning. Nevertheless, it is unclear how on-site educators of museums and environmental education centres perceive or address supporting students’ career awareness. We aimed to explore how Estonian on-site educators perceive the connection between curricula-related learning at their institutions and students’ career awareness (namely, work-related knowledge and self-awareness). The qualitative data are drawn from two datasets: (1) 27 out-of-school educators chosen by purposeful sampling participated in focus-group interviews about their practice; (2) 43 out-of-school educators filled out open-ended online surveys on career awareness education. Qualitative content analysis was used to find meaningful patterns from the dataset. Various specific examples of work-related learning activities emerged. However, career awareness was often understood narrowly or had not been previously conceptualised: students’ self-awareness was seldom explicitly perceived as part of career awareness. Moreover, supporting students’ lifelong learning or the development of sustainability competencies was explicitly emphasised only by more experienced or outstanding on-site educators.